2007
DOI: 10.1002/eji.200636855
|View full text |Cite
|
Sign up to set email alerts
|

In vivo disruption of T cell development by expression of a dominant‐negative polypeptide designed to abolish the SLP‐76/Gads interaction

Abstract: Multi-molecular complexes nucleated by adaptor proteins play a central role in signal transduction. In T cells, one central axis consists of the assembly of several signaling proteins linked together by the adaptors linker of activated T cells (LAT), Src homology 2 domain-containing leukocyte-specific phosphoprotein of 76 kDa (SLP-76), and Grb2-related adaptor downstream of Shc (Gads). Each of these adaptors has been shown to be important for normal T cell development, and their proper sub-cellular localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Our previous data suggested that the signaling pathways controlled by the Gads/SLP76 complex also include those regulating adhesion processes (22). In this study, we confirm this hypothesis by showing that suppression of SLP76 expression by RNAi in human T cells or the Lysates were analyzed by Western blotting using the indicated Abs.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our previous data suggested that the signaling pathways controlled by the Gads/SLP76 complex also include those regulating adhesion processes (22). In this study, we confirm this hypothesis by showing that suppression of SLP76 expression by RNAi in human T cells or the Lysates were analyzed by Western blotting using the indicated Abs.…”
Section: Discussionsupporting
confidence: 83%
“…In line with this idea is the observation that disruption of the interaction between SLP76 and Gads blocks TCR-mediated adhesion to ICAM-1 (22). Furthermore, it was shown that mutation of those tyrosine residues within ADAP, which are believed to mediate the interaction between ADAP and SLP76, blocks TCR-mediated activation of LFA-1 (23).…”
Section: Src Homology 2-domain Containing Leukocyte-specific Phosphopmentioning
confidence: 81%
See 2 more Smart Citations
“…Disruption of upstream components such as p56lck, ZAP-70, LAT, SLP-76 or GADS-SLP-76 interaction results in a generic impairment of LFA-1-mediated adhesion [17][18][19] (Figure 2). A recent study has shown that a polypeptide identical to the site on SLP-76 that binds to GADS can also inhibit TCR-induced integrin adhesion and thymocyte development [20].Despite the importance of these general upstream events, the quest over the past few years has been to identify the key downstream effector adaptors of the 'inside-out' adhesion pathway. A major advance in this area has recently come with the discovery of immune-cell adaptors ADAP [previously known as Fyn T-binding protein ( …”
mentioning
confidence: 99%